Floods and reservoir safety (ICE Publishing, 2015)
"This fourth edition of Floods and reservoir safety provides authoritative guidance on flood protection standards, flood magnitude and freeboard, which is essential for engineers who are responsible for the design and inspection of reservoirs"--Page 4 of cover